Key Plant, Key Pests: Pine Species (Pinus sp.) - Juanita Popenoe; Jacqueline Bourdon; Caroline R. Warwick; Chris Marble (EDIS, 2018)
This series of Key Plant, Key Pests publications are designed for Florida gardeners, horticulturalists and landscape professionals to help identify common pests associated with common Florida flora. This publication, the seventh in the Key Plant, Key Pests series, helps identify the most common pests found on Pinus sp.